2007
DOI: 10.1002/adma.200601528
|View full text |Cite
|
Sign up to set email alerts
|

High‐Modulus Spin‐On Organosilicate Glasses for Nanoporous Applications

Abstract: Nanoporous glasses, that is, structural glasses with large quantities of nanoscale porosity, are the cornerstone of several emerging technologies. The most prominent example is the semiconductor industry where interlayer dielectric (ILD) insulator films are critically needed to both reduce the resistance-capacitance time delay of the interconnect circuitry and reduce the cross-talk between adjacent conduction lines. For next-generation semiconductors these materials need an ultralow dielectric constant (k < 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 28 publications
(34 reference statements)
5
59
0
Order By: Relevance
“…Nevertheless, it was observed that at a dielectric constant of ∼2.3, the Young's modulus doubles when the MTMS/BTASE ratio is increased from 100:10 to 100:90 [169]. This result is in good agreement with a study on neat films showing the significant impact on the Young's modulus of adding 10 to 100 mol % of BTASE to MTMS [172]. Still, the addition of porosity to MTMS/BTASE copolymers leads to an important decrease of the mechanical properties, even at low porogen loadings.…”
Section: Hybrid Organic-inorganic: Oxycarbosilanessupporting
confidence: 87%
“…Nevertheless, it was observed that at a dielectric constant of ∼2.3, the Young's modulus doubles when the MTMS/BTASE ratio is increased from 100:10 to 100:90 [169]. This result is in good agreement with a study on neat films showing the significant impact on the Young's modulus of adding 10 to 100 mol % of BTASE to MTMS [172]. Still, the addition of porosity to MTMS/BTASE copolymers leads to an important decrease of the mechanical properties, even at low porogen loadings.…”
Section: Hybrid Organic-inorganic: Oxycarbosilanessupporting
confidence: 87%
“…12 Existence of this peak indicates the presence of a highly symmetrical molecular structure such as closed cage. The peak at around 1050 cm À1 is attributed to the (Si-O) 4 ring symmetric stretch vibration mainly from asymmetric random network structures such as open cage and short ladder. 12 Indeed, the IR spectrum of a commercial octamethyl POSS, which is a well-defined and highly symmetric T8 cage, has one strong, narrow Si-O stretching band at 1107 cm À1 instead of two broader Si-O stretching bands.…”
Section: Introduction Of Conventional Infrared Analysis On Sol-gel Simentioning
confidence: 98%
“…Based on quantum calculation, there should be a broad distribution in the number of Si-O tetrahedron per ring. 11 Relatively, the (Si-O) 4 and (Si-O) 6 rings are more predominating and thus have been better studied among all the Si-O rings. The (Si-O) 4 ring forms several structures such as open cage, closed cage, and ladder.…”
Section: Introduction Of Conventional Infrared Analysis On Sol-gel Simentioning
confidence: 99%
See 2 more Smart Citations